Novel Deleterious Dihydropyrimidine Dehydrogenase Variants May Contribute to 5‐Fluorouracil Sensitivity in an East African Population. Issue 3 (26th November 2016) - Elraiyah, T; Jerde, CR; Shrestha, S; Wu, R; Nie, Q; Giama, NH; Sarangi, V; Roberts, LR; Offer, SM; Diasio, RB
Abstract : Clinical studies have identified specific genetic variants in dihydropyrimidine dehydrogenase (DPD; DPYD gene) as predictors of severe adverse toxicity to the commonly used chemotherapeutic 5‐fluorouracil (5‐FU); however, these studies have focused on European and European‐American populations. Our laboratory recently demonstrated that additional variants in non‐European haplotypes are predictive of 5‐FU toxicity. The objective of this study was to identify potential risk variants in an understudied East African population relevant to our institution's catchment area. The DPYD protein‐coding region was sequenced in 588 individuals of Somali or Kenyan ancestry living in central/southeast Minnesota. Twelve novel nonsynonymous variants were identified, seven of which significantly decreased DPD activity in vitro . The commonly reported toxicity‐associated variants, *2A, D949V, and I560S, were not detected in any individuals. Overall, this study demonstrates a critical limitation in our knowledge of pharmacogenetic predictors of 5‐FU toxicity, which has been based on clinical studies conducted in populations of limited diversity.